Waist circumference percentile in children from municipalities of developed and developing countries - Andaki,Alynne Christian Ribeiro (2017)
Abstract Aims: to design reference percentile curves of waist circumference (WC) in children aged 6-10 from municipalities of developed (Portugal) and developing (Brazil) countries and to compare these results with other international references. Methods: this cross-sectional study enrolled a 6-10-year-old probability sampling. Univariate analysis of covariance adjusted by height was carried out to test the main effects of age, sex, countries, and interactions. WC percentile curves were performed with the LMS Chart Maker. Results: The sample comprised 6,475 children. Portuguese children presented a curvilinear increase in WC curves and Brazilian WC curves have shown a linear increase with age both for boys and girls. Overweight and obesity prevalence was 15.9 % and 4.7 % for Portuguese children and 12.9 % 4.5% for Brazilian children, respectively. There was a main effect (p<0.0001) for age and countries, and an interaction effect for sex*age (p=0.001) and countries*age (p<0.0001). Portuguese boys and girls have shown higher values for the 50th, 75th, and 95th percentiles than Brazilian boys and girls. Conclusions: WC reference percentile curves were drawn for 6-10-year-old Portuguese and Brazilian children. Portuguese children have higher WC values than Brazilian children and other children from developed countries.